Efflurage Massage For Mothers With Latent Phase I Labour Pain At Sikumana Health Centre - Wulandari, Jessica Putri; Kapita, Meiyeriance; Kleden, Simon Sani (Jurnal EduHealth, 2024)
Background: Labor and delivery of a baby is a normal process for women of childbearing age and women experience pain during labor is a physiological process of datta from the puskesmas sikumana Kupang City shows that, The number of Trimesster-III mothers. K4. In 2023 at the Sikumana health center there were 1111 people, in 2024 from January to May there were 435 people. Case Study Objectives: This case study aims to determine the action of efflurage massage therapy to reduce pain in mothers in labor during the 1st latent phase at Sikumana Health Center. Methods: This case study design is a type of qualitative case study. This qualitative case study research includes an intensive study of one research unit such as one client, family, group, community or institution. Results: The results obtained the number of research respondents were 2 people with female gender. The research was conducted on 24 June - 01 July 2024 in the ponek room of the Sikumana Kupang health center. Conclusion: From the results of the examination after 8 hours given the efflurage massage technique, it can be said that the efflurage massage technique is effective for reducing pain in laboring women in the first stage of the latent phase.